Implementasi UU Nomor 39 Tahun 2004 terhadap Tenaga Kerja Indonesia di Luar Negeri - Vinni Dini Pratiwi; Suharno Suharno (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
Indonesian labor is a term for low-skilled and unskilled Indonesian citizens who work abroad in employment relations for a certain period of time with wages. Legal protection for Indonesian Workers' Rights has not gone well, the need for guidance on the meaning of labor law for Indonesia, this undermines Indonesian Workforce and eliminates job security for Indonesian workers while abroad, the obstacles to implementing Indonesian legal protection for workers are mistakes that conducted by Indonesia, namely Manpower does not report problems to the Government of Indonesia in connection with the employment of Indonesian Workers. The purpose of this research is to find out more clearly and broadly about the protection of Indonesian workers working abroad who are carried out by the terrace of the Ministry of Placement of Protection of Indonesian Workers in North Sumatra Province. The method carried out in this study is descriptive qualitative methods related to data collection and identification. Data analysis method uses data reduction and research instruments, namely interviews and documentation. The results of this study indicate that the Indonesian Labor Protection Placement Service has carried out its duties with the policy of Law No. 39 of 2004 concerning the placement and protection of Indonesian workers abroad. In carrying out its duties there are obstacles faced in providing legal protection to the state labor force.